Sketsa Dakwah Islam di Eropa Barat - Aliyudin Aliyudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2008)
The history of Dakwah in West-Eropa can be devided in two patterns: The first, from century 8th to 15th , named at least as politic dakwah. Muslims have real authority in some areas: a few islands in midle sea and minor place in south-Italia and Franch, nor Spanish and Sicilia. The second, sine 19th century till now, muslims haven’t political authority. The pattern of dakwah only depend on profile, personality, performance of muslim imigrans behavior as worker, trader, student, diplomat, ect.